Solvent-Free Approaches for the Synthesis of Lophine Derivatives - Desai, Shiv R.; Modha, Sachin G. (Sustainability & Circularity NOW, 2024)
Solvent-free synthesis comes with many advantages such as cost reduction, waste reduction, ease of operation, sustainability, environmentally benign operations, etc. These benefits have prompted many chemists to develop new protocols for solvent-free synthesis of various interesting chemical compounds. One such class of compounds is 2,4,5-triarylimidazoles, commonly known as lophines due to their applications in materials science, chemo- and bio-sensors, and pharmacology. This article focuses on solvent-free synthesis of lophine derivatives via different protocols, including the use of inorganic-, organic-, and biocatalysts; solid-supported catalysts; microwave-mediated heating; and grinding.
Keywords: Lophine; Triaryl imidazoles; Imidazoles; Solvent-free; Neat; Sustainable chemistry; Green chemistry; Multicomponent reactions